Ectomycorrhizal communities in a Mediterranean forest ecosystem dominated by Quercus ilex: seasonal dynamics and response to drought in the surface organic horizon - Richard, Franck; Roy, Melanie; Shahin, Oula; Sthultz, Christopher; Duchemin, Myriam; Joffre, Richard; Selosse, Marc-André (Annals of Forest Science, 2011)
• Introduction Millions of hectares of Quercus ilex forests dominate disturbed landscapes in the western part of the Mediterranean basin. Although these forests are very widespread, little is known about the composition and structure of their associated ectomycorrhizal fungal communities. • Results and discussion We examined seasonal patterns in ectomycorrhizal communities and their response to increased drought using a rainfall exclusion experiment established in a Q. ilex coppice since 2003. Ectomycorrhizae were sampled four times in 2007–2009. By sequencing fungal ITS, we identified 129 species in 1,147 sequenced ectomycorrhizal root tips. The fungal community in the surface organic horizon was well described by the logseries theoretical model, with 47.9% of singleton species. The composition of the community was strongly dominated by Basidiomycetes, with three families (Thelephoraceae, Russulaceae and Cortinariaceae) accounting for 72.9% of the root tips. Relative abundance of Russulaceae and Thelephoraceae showed pronounced seasonal shifts. Experimental reduction of rainfall resulted in significant shifts in community composition and seasonal fluctuations but had no effect on global richness of the community. • Conclusions Together, these results suggest that the predicted rainfall reduction in this region due to climate change will lead to shifts
Keywords: Drought; ectomycorrhizal communities; Global change; Mediterranean forests